PROGRAMS FOR DATA REDUCTION AND OPTIMIZATION OF THE SYSTEM WORK - Breus, V. V. (Одеські астрономічні публікації, 2007)
During last years, some new computer programs were developed. In this article, will be described three of them. The "Variable Stars Calculator" was developed for processing photometrical observations of variable stars. It helps the observer at each step from converting estimates of brightness into stellar magnitudes to searching a period of changing brightness, PCA analysis, searching extremums by the polynomial approximation etc. The program has Ukrainian, Russian an English interface languages and it is possible to add new ones. The "PolarObs" was developed for processing polarimetrical observations, obtained at the 2.6 Shain telescope in the Crimean astrophysical observatory. It was used either for processing observations of cataclysmic variable stars, or for comets. "TrayDog" is a system tool for Windows with more than 50 functions. Enhanced Task manager, that can view and edit properties of process, windows, libraries, threads, network ports and opened files. Other functions are: switching between desktops by hot-key, minimize any window to the system tray area, system information, blocking pop-ups of any kind, view and connect network shared resources, alarm clock and other functions. The interface of the current version is only in Russian. These and some other programs can be downloaded from the pages http://uavso.org.ua/breus